Yeast Fermentate Prebiotic Ameliorates Allergic Asthma, Associating with Inhibiting Inflammation and Reducing Oxidative Stress Level through Suppressing Autophagy - Subo Gong; Xiaoying Ji; Jing Su; Yina Wang; Xianghong Yan; Guyi Wang; Bin Xiao; Haiyun Dong; Xudong Xiang; Shaokun Liu (Mediators of Inflammation)
Background and Purpose. Allergic asthma, a respiratory disease with high morbidity and mortality, is reported to be related to the airway allergic inflammation and autophagy-induced oxidative stress. Although the therapeutic effects of fermentate prebiotic (YFP) on allergic asthma have been widely claimed, the underlying mechanism is still unclear. This study is aimed at investigating the possible mechanism for the antiasthma property of YFP in a mouse model. Methods. Ovalbumin was used to induce allergic asthma following administration of YFP for one week in mice, to collect the lung tissues, bronchoalveolar lavage fluid (BLFA), and feces. The pathological state, tight-junction proteins, inflammatory and oxidative stress-associated biomarkers, and TLRs/NF-κB signaling pathway of the lung tissues were evaluated by HE staining, immunofluorescence, ELISA, and WB, separately. RT-PCR was used to test oxidative stress-associated genes. Leukocyte counts of BLFA and intestinal microbiota were also analyzed using a hemocytometer and 16S rDNA-sequencing, separately. Result. YFP ameliorated the lung injury of the mouse asthma model by inhibiting peribronchial and perivascular infiltrations of eosinophils and increasing tight-junction protein expression. YFP inhibited the decrease in the number of BALF leukocytes and expression of inflammatory-related genes and reversed OVA-induced TLRs/NF-κB signaling pathway activation. YFP ameliorated the level of oxidative stress in the lung of the mouse asthma model by inhibiting MDA and promoting the protein level of GSH-PX, SOD, CAT, and oxidative-related genes. ATG5, Beclin1, and LC3BII/I were significantly upregulated in asthma mice, which were greatly suppressed by the introduction of YFP, indicating that YFP ameliorated the autophagy in the lung of the mouse asthma model. Lastly, the distribution of bacterial species was slightly changed by YFP in asthma mice, with a significant difference in the relative abundance of 6 major bacterial species between the asthma and YFP groups. Conclusion. Our research showed that YFP might exert antiasthmatic effects by inhibiting airway allergic inflammation and oxidative stress level through suppressing autophagy.